Sophytes’ Helmet: Origin, Symbolism, and Apotheosis - Taylor, Lloyd W. H. (KOINON: The International Journal of Classical Numismatic Studies, 2021)
This study examines the development of the depiction of the helmet worn by the male head on the coinage of Sophytes and its implications for alternative theories of attribution of the coinage. This was an Attic military helmet of the 3rd century BC. It is presented in a numismatic depiction that evolved from the preceding portrayal of Athena’s helmet on the Series 2 imitative Athenian coinage struck under Andragoras of Parthia. Calibration of the changes in coin fabric and the details of the helmet depicted on the Series 2 coinage to identical developments in the Athenian coinage of the 3rd century BC serve to date its emission to the middle of the 3rd century BC. Detailed analysis reveals that the obverse iconography of the Sophytes’ coinage developed independently of the superficially similar obverse iconography of the victory issues of Seleukos I struck at Susa. Consequently, there is no basis for the frequently inferred chronological nexus between the two coinages. Furthermore, art history considerations suggest that Sophytes, via the ornamentation of his helmet, sought to assimilate his image with that of Ares, in a claim to divinity that can only have emerged in the mid-third century BC when Greek religious and cultural norms had evolved to accept the apotheosis of leaders. An examination of the imagery of the gold stater emission struck by Sophytes predecessor, Andragoras, identifies the precedent for Sophytes claim to divinity in a symbolic numismatic narrative that reflects the rising existential threat to the secessionist march state of Parthia posed by the invading Parni, led by Arsaces.